Temporalis Myofascial Flap and Conchal Bowl Cartilage Grafting for Temporomandibular Joint Arthritis - Anthony DeLeonibus, MD; Marco Swanson, MD; Demetrius M. Coombs, MD; Samantha Maasarani, MD, MPH; Francis Papay, MD; Bahar Bassiri Gharb, MD, PhD; Antonio Rampazzo, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Temporomandibular joint (TMJ) arthritis arises from a multitude of etiologies; however, there is no consensus definitive treatment. The complication profile of artificial TMJs is well known, and outcomes are variable and are reserved for salvage attempts. This case details a patient with persistent traumatic TMJ pain, arthritis, and single-photon emission computed tomography scan of potential nonunion. The present study reports on the first novel use of an alternative composite myofascial flap to help arthritic TMJ pain. This study details the successful use of a temporalis myofascial flap and conchal bowl autologous cartilage graft in posttraumatic TMJ degeneration.